Transfer matrix simulation of reflectivity of distributed Bragg Reflectors (DBRs) - Jose, Ameera A. (The Western Mindanao State University research journal, 2014)
A dialectric mirror known as distributed Bragg reflector (DBR) is commonly used as an essential element of an opto-electronic device. Opto-electronic devices such as lasers and LEDs provide great importance in recent technologies. With the aim of exploring technology as well as for pre-fabrication process of this mirror, computer simulation was implemented in order to identify the desired optical properties. In this study, four (4) DBR samples were examined, namely: GaAs/A1As, A1N/A10.23Ga0.77N, SiO2/HfO2, and ZnO/MgO. The researcher applied the transfer matrix method (TMM) technique to numerically simulate the reflectivity and angle-resolved reflectivity at different incident angles, specifically: θ_i=0°, 15° ,30° ,45° , and 60°. TMM technique calculates the reflectivity of the samples in a specified wavelength band (ranging from infrared to blue-UV spectral range). Parameters such as indices of refraction (n), center wavelength (λ_c), an incident angle (θ_i), and the number of pairs (N), were varied in the program. The four mirrors were compared according to the highest achieved reflectivity and spectral broadness at a given λ _c. The results showed that GaAs/A1As operates well in the infrared region (λ _c=885nm) with a reflectivity of R= 99.55% at N= 20 pairs. Materials in blue-UV range were also highly reflective at λ _c = 380nm. For A1N/A10.23Ga0.77N material, maximum reflectivity reached R = 94.2% at N = 30 pairs; SiO2/HfO2 and ZnO/MgO materials obtained R =97.1% and R =99.3%, respectively, with the least N = 9 pairs. For blue-UV range samples, ZnO/MgO had the highest reflectivity followed by SiO2/HfO2 and A1N/A10.23Ga0.77N. Finally, based from simulation, the study concluded that DBRs of different kinds have excellent optical properties depending on the nature and kind of materials used.